A receptor-like mechanosensitive protein governs preprophase band positioning for asymmetric cell divisions and SC morphogenesis - Zhikun Duan; Wenwen Duan; Zihao Zhang; Kaiwen Li; Suting Wang; Jiapeng Yang; Baolin Xiao; Tian Zhang; Jianchao Ma; Baozhu Li; Pengtao Wang; Yi Cao; et al. (Proceedings of the National Academy of Sciences, 2026)
Asymmetric cell division underpins cellular diversity in multicellular plants. These divisions are mechanosensitive, and preprophase band (PPB) formation hinges on cell-wall mechanical properties in plant cells. Yet, the spatial control mechanism governing this process in plants remains elusive. During grass stomatal development, mechanical cues originate from differential growth rates and cell wall modifications at the interface of guard mother cell/subsidiary mother cell (SMC). In this work, we have identified a maize receptor-like protein, KAI1, that functions as a master regulator of subsidiary cell formation within the stomatal complex. KAI1 governs division-plane orientation in SMCs through mechanochemical signaling: It perceives cell wall rigidity via pectin interaction, and subsequently recruits tubulin for PPB positioning, thereby directing division-plane specification. This work uncovers a plant-unique mechanosensitive protein that mediates extracellular matrix cues to cytoskeletal reorganization during asymmetric division for cell diversity. Our findings establish that KAI1 governs a cell wall mechanics-dependent PPB positioning to control the exact division plane alignment of the SMC. This mechanism subsequently mediates the regulation of SMC polarization and subsidiary cell morphogenesis during stomatal development.